ANALISIS MANAJEMEN LAYANAN E-LEARNING PADA PALCOMTECH BATURAJA DENGAN FRAMEWORK ITIL - Diana, Rosita; Kisworo, Marsudi Wahyu (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Palcomtech Baturaja is an educational institution that provides e-learning services and faces various challenges in its management to ensure an optimal learning experience for students and teachers. Therefore, this research aims to analyze the management of e-learning services at Palcomtech Baturaja by utilizing the ITIL (Information Technology Infrastructure Library) framework. E-learning is becoming increasingly important in education, especially in today's digital era. However, the success of e-learning implementation often depends on the effectiveness of the service management that supports it. In this context, the ITIL framework offers a structured framework for managing it services well. This research will carry out an in-depth analysis of existing e-learning service management practices at Palcomtech Baturaja, with a focus on the main aspects defined by ITIL, such as service strategy and continuous service improvement. The methodology applied in this research includes a literature review, interviews with related parties, distribution of questionnaires and direct observation of existing e learning systems. It is hoped that the findings of this research will provide valuable insights for Palcomtech Baturaja management to improve the efficiency and effectiveness of their e-learning services by implementing the ITIL framework.